2010
DOI: 10.1007/s00068-010-1048-7
|View full text |Cite
|
Sign up to set email alerts
|

Today’s Role of External Fixation in Unstable and Complex Pelvic Fractures

Abstract: The use of the external fixator for the initial and in some cases for the definitive fixation of unstable and complex pelvic injuries with hemodynamic instability is still a successful treatment of multiply injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Immobilizing pain is the most significant symptom, and hemodynamic instability is not present. For this reason, emergency stabilization with pelvic sheets, binders, C-clamps, or external fixators is not necessary [ 33 , 34 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Immobilizing pain is the most significant symptom, and hemodynamic instability is not present. For this reason, emergency stabilization with pelvic sheets, binders, C-clamps, or external fixators is not necessary [ 33 , 34 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…[1] Post-traumatic bowel entrapment was first described in 1907. [3] Since then, there have been only occasional reports in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an external fixator for the initial and, in some cases, the definitive fixation of unstable, complex pelvic injuries with hemodynamic instability is effective for multiply injured patients. [1]…”
Section: Introductionmentioning
confidence: 99%
“…In a study, the outcome of external fixator in pelvic fractures was found to be satisfactory (anatomical and functional outcome) achieved in 16 of 20 cases (80%). 6 Although the type of fracture, the quality of the bone, the fixator design of the , the patient's habitus, the number and size of the pins, quality, maintenance of the technique, and other factors all influence external fixation stability. 7 The study has been conducted to assess the magnitude of outcome of external fixator in pelvic fracture as local data is not adequate on this topic, so this study will generate local data and if the outcomes found to be satisfactory then the same modality was used in such cases.…”
Section: Introductionmentioning
confidence: 99%